Configuration‐dependent anionic redox in cathode materials. Issue 2 (24th March 2022) - Yang, Lu; Chen, Rusong; Liu, Zepeng; Gao, Yurui; Wang, Xuefeng; Wang, Zhaoxiang; Chen, Liquan
Abstract: The utilization of anionic redox is one of the most prospective strategies to obtain high specific capacities in addition to the transition metal redox. The specific local environments around the oxygen atoms lead to the transference of the oxygen electrons with different difficulties for the excess capacity of the cathode materials. Nevertheless, the structural and performance degradation is closely related to the irreversible anionic redox, resulting in serious challenges for the commercialization of the cathode materials. Therefore, it is necessary to summarize the correlation between the oxygen configuration for the anionic redox and the resultant structural features to better utilize the anionic redox for the cathode materials with better performances. This review summarizes the latest advances of oxygen redox in the cathode materials in terms of their oxygen configurations. First, the fundamental mechanisms of anionic redox are discussed. On the basis of the local atoms and configurations, the recent strategies are then discussed that are promising to boost the reversibility of the anionic redox and mitigate the side reaction triggered by the oxygen redox. At last, an outlook is presented on the strategies to optimize the reversibility of the anionic redox for achieving the high energy‐density cathode materials. Abstract : Anionic redox is one of the most promising strategies to boost the high specific capacity in addition to the conventional transition metal redox. The various configurations around oxygen atoms facilitate the transference of electrons with different difficulties for the oxygen redox in cathode materials. This review summarizes the mechanisms of the anionic redox with different configurations and discusses the possible strategies for boosting the reversibility of the anionic redox and mitigating the side reaction triggered by the oxygen redox.